Workshop Cybersecurity Awareness Meningkatkan Literasi Keamanan Digital di Wilayah Suburban Kepulauan Riau - Nelmiawati, Nelmiawati; Fani, Maidel; Arif, Hamdani; Khaira, Hajrul; Ramadhan, Gilang Bagus; Afif, Iqbal (Politeknik Negeri Batam, 2023)
Phishing attack works by deceiving the victim so that they give their asset such as credential information to the attacker. The high level of cybercrime in form of phishing after COVID-19 pandemic has increasingly affected. It reaches new quarterly high in late 2022, where there was more than 4.7 million of phishing attacks has been launched, based on Anti-Phishing Work Group (APWG) Phishing Activity Trends Report. The importance of knowledge about phishing awareness is very necessary to minimize the affected victim. In order to decrease the issue, a Cybersecurity Awareness workshop has been conducted at several schools in Batam suburban area; SMK Negeri 1 Batam, SMK Multistudi High School (MHS) Batam, and SMK Negeri 1 Tanjung Pinang. The aim of these activity is to increase cybersecurity public awareness of phishing attack from an early age, especially at schools. As an approach, several activities related to phishing awareness have been executed in a workshop, including phishing simulation as well as socialization. Based on these activities, results shown that phishing awareness has been achieved in average 70% currently at young age.